1992
DOI: 10.1046/j.1537-2995.1992.32292180144.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prestorage white cell‐reduction of apheresis platelets on platelet glycoprotein Ib and von Willebrand factor

Abstract: Twenty plateletpheresis components were harvested from 11 healthy donors and stored in polyolefin bags on a horizontal flatbed agitator at 22 degrees C. After 24 hours, white cells were reduced in one aliquot by centrifugation while the other aliquot was stored unaltered. Samples were obtained aseptically from each of these platelets at intervals for up to 10 days, and measurements were made of platelet glycoprotein Ib (GPIb) by both flow cytometry and polyacrylamide gel electrophoresis, of ristocetin-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
5
10
0
Order By: Relevance
“…We con clude that the concentration of neutrophil granulocytes was about hundred times lower than 1,000/pl in our PCs. This would explain the absence of a beneficial effect of prestor age leukocyte depletion on poststorage platelet function in our investigation as well as in the papers mentioned above [18,23,28]. The authors of these studies did not perform differentials either, but we assume that the lymphocyteigranulocyte ratio in their PCs was similar to that observed in our laboratory.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We con clude that the concentration of neutrophil granulocytes was about hundred times lower than 1,000/pl in our PCs. This would explain the absence of a beneficial effect of prestor age leukocyte depletion on poststorage platelet function in our investigation as well as in the papers mentioned above [18,23,28]. The authors of these studies did not perform differentials either, but we assume that the lymphocyteigranulocyte ratio in their PCs was similar to that observed in our laboratory.…”
Section: Discussionsupporting
confidence: 80%
“…We conclude that there is no ad vantage evident in terms of improved platelet quality for prestorage leukodepletion of PCs. This is in accordance with the results of other studies; neither Sweeney et al [28], who investigated apheresis platelet concentrates with a median leukocyte contamination of 2x 107 before filtration, nor Joustra-Dijkhuis et al [18], who examined platelet con centrates made from a pool of four buffy coats with a mean leukocyte contamination of 7.2xl06 before filtration, nor Garcia et al [23], who investigated apheresis platelets with a mean leukocyte contamination of 12.2 xlO8 could demon strate a beneficial effect of prestorage leukocyte depletion of PCs on poststorage platelet quality. In contrast to Dzik et al [14], who examined PRP with a much higher leukocyte mission in the turbidimetric assay.…”
Section: Storage Of Leukocyte Depleted Platelet Concentratessupporting
confidence: 89%
See 1 more Smart Citation
“…Our results show that the binding of specific MoAbs to GPIb and GPIIb/IIIa was similar in NFPCs and FPCs and that it was stable during 7 days of storage. These results are in agree-ment with those of Garcia et al [29] who analyzed GPIb of stored apheresis platelets by sodium dodecyl sulfate PAGE. Other authors found a significant diminution of GPIb and a decrease of platelet responsiveness to ristoce tin in stored PCs enriched by relatively high amounts of neutrophils (1 x KT/ml) compared to platelet stored with out enrichment, but they failed to demonstrate such an effect in PCs enriched by lymphocytes (lxl01 2 3 4 5 6 7/ml) [30], Our results probably reflect the low leukocyte content in PCs prepared by the 'surge' technique.…”
Section: Discussionsupporting
confidence: 92%
“…Several investigators have shown that vWf is a substrate for leukocyte-derived proteases [64, 67]. Though platelet-derived vWf degrading proteases have been documented [68], Garcia et al [69]also showed that plasma vWf was stable in leukocyte-poor suspensions of platelets. This suggests that platelet-derived proteases do not play a significant role in vWf degradation under blood bank conditions.…”
Section: Discussionmentioning
confidence: 99%